INGCREASING MICRO SMALL MEDIUM ENTEPRISES ACTIVITY ENTREPRENEURIAL CAPACITY IN THE FIELD OF DIGITAL MARKETING - Fachrurazi Fachrurazi; Zarkasi Zarkasi; Sofia Maulida; Rianda Hanis; Muhammad Yusuf (SEAN Institute, 2022)
The advancement of technology, information, and communication causes changes in all aspects of life, including entrepreneurship. Over time, the world of entrepreneurship will continue to develop and use digital technology as a medium for marketing activities. This study aims to help activists in the creative industry improve their digital marketing skills. The research method used is qualitative with a descriptive approach, and it is located in Pekanbaru City. Data collection methods include observation, in-depth interviews, and documentation. Huberman and Miles classify qualitative data analysis techniques as descriptive. The findings of this study provide an opportunity for entrepreneurs to increase their capacity in the field of entrepreneurship by first understanding three concepts. First, entrepreneurs must consider market segmentation because it can serve as the foundation for the company's digital marketing strategy. Second, create messages that are tailored to the target audience, and third, tailor messages to which media or channel will be used later. Understanding these three concepts can help entrepreneurs increase their entrepreneurial capacity in the digital field.